2015
DOI: 10.1021/acschembio.5b00368
|View full text |Cite
|
Sign up to set email alerts
|

Chemoproteomics Reveals Novel Protein and Lipid Kinase Targets of Clinical CDK4/6 Inhibitors in Lung Cancer

Abstract: Several selective CDK4/6 inhibitors are in clinical trials for non-small cell lung cancer (NSCLC). Palbociclib (PD0332991) is included in the phase II/III Lung-MAP trial for squamous cell lung carcinoma (LUSQ). We noted differential cellular activity between palbociclib and the structurally related ribociclib (LEE011) in LUSQ cells. Applying an unbiased mass spectrometry-based chemoproteomics approach in H157 cells and primary tumor samples, we here report distinct proteome-wide target profiles of these two dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 31 publications
(74 reference statements)
4
80
0
Order By: Relevance
“…Consistent with the gene silencing, the dual CAMKK2/AMPK inhibitor compound C did not synergize with paclitaxel. In addition, combination of paclitaxel with the CDK4/6 inhibitor ribociclib, which has no activity against RSK1/2, IGF1R, or FAK1, 37 did not exhibit synergy, whereas the FAK1/RSK/IGF1R inhibitor CEP-37440 38 strongly synergized with paclitaxel (Supplementary Fig. 7e–f).…”
Section: Resultsmentioning
confidence: 98%
“…Consistent with the gene silencing, the dual CAMKK2/AMPK inhibitor compound C did not synergize with paclitaxel. In addition, combination of paclitaxel with the CDK4/6 inhibitor ribociclib, which has no activity against RSK1/2, IGF1R, or FAK1, 37 did not exhibit synergy, whereas the FAK1/RSK/IGF1R inhibitor CEP-37440 38 strongly synergized with paclitaxel (Supplementary Fig. 7e–f).…”
Section: Resultsmentioning
confidence: 98%
“…In a recent study on lung cancer, palbociclib was shown to interact with several protein and lipid kinases beyond CDK4/6 (23). Based on this report and our unexpected finding in Figure 2A, we performed screening for other potential targets with a commercial antibody array kit.…”
Section: Resultsmentioning
confidence: 99%
“…An alternative approach defines the array of biophysical interactions that a drug is capable of making which enables the connection to a wealth of known physiology. Previously, subsets of CDK drugs have been studied (41,(47)(48)(49) with more systematic comparisons occurring by literature reviews (4,9,19). In the current study, a synergistic combination of cellular, biochemical, and crystallographic analysis is used to characterize multiple generations of CDK drugs in a single study.…”
Section: Discussionmentioning
confidence: 99%
“…The kinome interaction assessments (purified proteins, tumor cell lysates) identify CDK9 as a likely candidate that contributes to abemaciclib's clinical pharmacology. It should be noted that another chemoproteomic study came to a different conclusion of about CDK9 selectivity but it used structural analogues of the CDK drugs to capture interacting kinases which could introduce kinase selectivity artifacts (47). Abemaciclib has significant biochemical potency for CDK5 so engagement of the atypical CDKs cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%